Interacting effects of physical and cognitive loads on walking gait - Chia, Avian Yuan Kai. (2013)
Falls are common and often a devastating problem especially amongst the elderly, causing a substantial amount of morbidity, mortality and extensive use of health care services such as premature nursing home admissions. Majority of these falls are associated with one or more identifiable risk factors (e.g. unsteady gait), and studies has shown that the rates of falling can be significantly reduced when attention are shown to these risk factors. 2 groups of participants were studied upon, namely the elderly participants and the young participants. 14 healthy young participants and 15 healthy elderly participants of various heights and weights participated in the experiment, which consisted of 15 different protocols, required to be completed in a 2.5 hour session. The aim of the study was to study the dual task effects of cognitive tasks and physical load carriage on level walking. Results for the anterior-posterior margin of stability (MOS) were the main concerns in this study, the MOS was used to quantify the gait stability while performing these protocols, also to find out which component in the working memory model would affect walking gait more significantly. It can be said that gait stability was significantly affected with the factor of age difference, where the elderly are physically less abled in comparison with the young. Utilisation of the VSSP and the phonological store (under the phonological loop component) of the working memory model was more significant in affecting the lower anterior-posterior MOS as compared to the central executive and articulatory rehearsal components of the working memory model. The conclusions derived from this project serve well to the future researchers and engineers, especially those who are working on the field of human factors and ergonomics, to understand causes and effects of gait instability and in developing interventions to minimize the risk of falls especially amongst the elderly.